Validation of the name Aristolochia compressicaulis and lectotypification of A. championii and A. punjabensis (Aristolochiaceae) - Do, Truong Van; Neinhuis, Christoph; Wanke, Stefan (Phytotaxa, 2015)
Aristolochia Linnaeus (1753: 960) subg. Siphisia (Rafinesque 1828: 62) Duchartre (1854: 29) (Aristolochiaceae) comprises about 70 species, 50 of which occur in East and South Asia while the remaining species occur from Central- to North America (Wagner et al. 2012, 2014, González et al. 2014). In this study, the taxonomic history of A. championii Merrill & Chun (1940: 47) and A. punjabensis Lace (1911: 273) is discussed, and the lectotypes for these two species are designated. Additionally, the name A. compressicaulis Yang (1988: 32) is validated by designating the holotype.